1995
DOI: 10.1111/j.1476-5381.1995.tb15919.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a selective 5‐HT1Areceptor antagonist and an SSRI in vivo: effects on 5‐HT cell firing and extracellular 5‐HT

Abstract: 1 The acute inhibitory effect of selective 5-hydroxytryptamine (serotonin) reuptake inhibitors (SSRIs) on 5-HT neuronal activity may offset their ability to increase synaptic 5-HT in the forebrain.2 Here, we determined the effects of the SSRI, paroxetine, and a novel selective 5-HTIA receptor antagonist, WAY 100635, on 5-HT cell firing in the dorsal raphe nucleus (DRN), and on extracellular 5-HT in both the DRN and the frontal cortex (FCx). Extracellular electrophysiological recording and brain microdialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
215
1
6

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(247 citation statements)
references
References 32 publications
25
215
1
6
Order By: Relevance
“…Similar to results obtained in vitro by Fletcher et al (1996), WAY 100,635 (at doses p100 mg/kg, i.v.) in the rat did not alter the firing activity of DR 5-HT neurons, although occasionally, WAY 100,635 produces some increases of the firing activity of DR 5-HT neurons without, however, achieving statistical significance Gartside et al, 1995;Fletcher et al, 1996;Lejeune and Millan, 1998). Mundey et al (1996) reported consistent increases in 5-HT neuronal firing in anesthetised guinea-pig, but apparently in 5-HT neurons firing at a very slow rate, on average 0.6 Hz.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to results obtained in vitro by Fletcher et al (1996), WAY 100,635 (at doses p100 mg/kg, i.v.) in the rat did not alter the firing activity of DR 5-HT neurons, although occasionally, WAY 100,635 produces some increases of the firing activity of DR 5-HT neurons without, however, achieving statistical significance Gartside et al, 1995;Fletcher et al, 1996;Lejeune and Millan, 1998). Mundey et al (1996) reported consistent increases in 5-HT neuronal firing in anesthetised guinea-pig, but apparently in 5-HT neurons firing at a very slow rate, on average 0.6 Hz.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, at 5-HT terminals where 5-HT levels are much lower than around the cell body, local infusion of a 5-HT autoreceptor antagonist increases 5-HT release as a result of lifting the dampening action of 5-HT on this 5-HT 1B autoreceptor (de Groote et al, 2003). Unexpectedly, however, the potent and selective 5-HT 1A antagonist WAY 100,635 ((N-{2-[4(2-methoxyphenyl)-1-piperazinyl]ethyl}-N-(2-pyridinyl)cyclohexanecarboxamide trihydroxychloride) when injected on its own in anesthetized rats has not consistently been reported to enhance the firing rate of 5-HT neurons Forster et al, 1994;Mundey et al, 1994;Gartside et al, 1995;Lejeune and Millan, 1998;Haddjeri et al, 1998;Martin et al, 1999;Hajós et al, 2001). Only in very active freely moving cats, when 5-HT neurons are firing at their highest rate, WAY 100,635 produces a clear disinhibition of 5-HT neuronal activity .…”
Section: Introductionmentioning
confidence: 99%
“…Since SSRIs produce a tonic elevation of serotonin levels in the extracellular space (Fuller, 1994;Malagié et al, 1995), their therapeutic effect is probably mediated, at least in part, by action at various levels of the serotonergic system, notably at serotonergic receptors (Barnes and Sharp, 1999). In particular, it has been proposed that the antidepressant effects of SSRIs would be related to desensitization of somatodendritic 5-HT 1A and terminal 5-HT 1B autoreceptors (Blier et al, 1987;Artigas et al, 1994Artigas et al, , 2001Pineyro and Blier, 1999), which is induced by and participates indirectly in the increase in 5-HT concentration in the extracellular space (Gartside et al, 1995(Gartside et al, , 1999Sharp et al, 1997;Trillat et al, 1998;Adell et al, 2001;Malagié et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, this effect was very moderate, and the administration of WAY-100635 failed to augment the effect of milnacipran in frontal cortex. WAY-100635 markedly enhanced the 5-HT elevations induced by SSRIs and clomipramine in this brain region (Gartside et al 1995;Malagié et al 1996;Romero et al 1996;Invernizzi et al 1997;. This effect results from the antagonism of the indirect actions of the SSRIs at raphe 5-HT 1A autoreceptors, as shown by the local application of WAY-100635 in the dorsal raphe nucleus (Romero and Artigas 1997).…”
mentioning
confidence: 95%
“…The baseline 5-HT output was unaffected by 2-week treatments with milnacipran (30 and 60 mg/kg и day). The distinct regional profile and the lack of enhancement of its effects by WAY-100635 and prolonged treatment suggest that milnacipran does not exert itsThe administration of selective 5-HT reuptake inhibitors (SSRIs), monoamine oxidase inhibitors (MAOIs), and clomipramine markedly increases the extracellular concentration of 5-HT in the raphe nuclei of the midbrain (Adell and Artigas 1991; Bel and Artigas 1992;Invernizzi et al 1992;Celada and Artigas 1993;Gartside et al 1995;Malagié et al 1995). In all instances, these elevations are superior to those produced in frontal cortex or, when examined, in hippocampus.…”
mentioning
confidence: 99%